Chicken Bone Ingestion Leads to Aortoesophageal Fistula With Catastrophic Bleeding - Raissa Nana Sede Mbakop MD; Jamil Shah MD; Arnold Forlemu MD; Vijay Gayam MD; Praneeth Bandaru MD; Vikash Kumar MD; Madhavi Reddy MD (SAGE Publishing, 2023)
Aortoesophageal fistula (AEF) is an uncommon, but potentially fatal cause of upper gastrointestinal bleeding. Aortoesophageal fistulas caused by foreign body ingestion are rare but devastating. The classic clinical triad of AEF consists of mid-thoracic pain or dysphagia, a herald episode of hematemesis, followed by fatal exsanguination after a symptom-free period (Chiari's triad). Computed tomography angiography (CTA) is the preferred diagnostic tool for identifying AEF and is substantially more sensitive than upper endoscopy for detecting AEF. Endoscopy can detect AEF as it might show pulsatile blood, pulsatile mass, hematoma, or adherent blood clot in the esophagus, or a deep esophageal tear. However, endoscopy has a low sensitivity and may delay definitive treatment. Several management options for AEF have been suggested; however, the definitive treatment is surgery performed on the thoracic aorta and esophagus, including esophagectomy, surgical replacement of the thoracic aorta, thoracic endovascular aortic repair, or omental flap. We report a case of a 63-year-old man who presented with hematemesis 2 weeks after chicken bone ingestion.